Optimizing enzymatic dyeing of wool and leather - Barros, Alexandre António Antunes (2019)
This work reports on the environmental friendly enzymatic dyeing of wool and leather performed at low temperature and mild pH conditions without any dyeing auxiliaries. The substrates have been dyed with “in situ” generated pigment by means of laccase-catalyzed oxidative coupling of dye modifier 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) and dye precursor 1,3-benzenediol in a batchwise process. The process reaction variables (laccase, precursor and modifier concentrations, temperature and dyeing time) were optimized by response surface methodology using an appropriate experimental design. The temperature, precursor concentration, interaction between precursor and modifier and time are the most important factors in the dyeing process. The best-optimized wool dyeing conditions (2 h reaction time, 50 μl laccase (0.1 U), 500 mM precursor, 10 mM modifier at 40 °C) were then successfully applied onto leather material. The enzymatic-dyeing optimized process can be successfully performed on wool and leather at low temperature and mild pH obtaining different hues and depths of shades by varying the modifier concentration and time. The colouring enzymatic system has a good reusability (which has a huge advantage in terms of cost reduction) and washing durability and is comparable in terms of fastness properties to the traditional dyeing process for both wool and leather.